Strength Properties Of Food Semi-Finished Products - Urinov Nasillo Fayzilloevich; Amonov Mahmud Idris ugli; Sokhibov Ibodullo Adizmurodovich; Sayliev Ismat Ismatovich (Zien Journals, 2022)
The article covers experimental study of knives with different sharpening angles to determine the strength properties of molded half-finished product and associated energy consumption for cutting. Determination of the values of the limiting shear stress of products depending on moisture content of the dough and the radius of rounding of the knife.
Keywords: cutting; strength properties; impact strength; blade knife